Bactericidal, fungicidal and anthelmintic activities of Alstonia scholaris bark extracts - Naveen Kumar H N,; Badarinath D Kulkarni,; JOY HARRIS HOSKERI,; Shruthi S. D,; Tarveen Jandoo,; Vedamurthy A B, (International Journal of Phytomedicine, 2013)
Plant based medicines are effective against many human infectious diseases either by paralysing or killing the pathogen. In the present study, petroleum ether, chloroform, ethanol and aqueous extracts of Alstonia scholaris bark were screened for their bactericidal, fungicidal and anthelmintic properties. Antibacterial activity revealed that chloroform extract at the 20 mg/ml showed significant antibacterial effect. Nevertheless, petroleum ether, ethanol and aqueous extracts also showed antibacterial effect against E. coli and S. dyscentreae, but less effective than chloroform extract. All the extracts were not as potent as the standard drug ciprofloxacin. Fungicidal activity revealed that among all the test extracts, ethanol extract at 20 mg/ml showed significant fungicidal effect against Rhizopus. . Interestingly, petroleum ether and ethanol extracts at 20 mg/ml showed more significant fungicidal action when compared to standard drug sulphamethoxazole. Anthelmintic activity of A. scholaris extracts was carried out at four different concentrations viz., 2.5, 5.0, 10.0 and 20.0 mg/ml to evaluate their effect in inducing paralysis and death in Pheretima posthuma. Anthelmintic activity revealed that petroleum ether extract at 20 mg/ml induced paralysis in worms within 12 min and death within 25.33 min. However, chloroform, ethanol and aqueous extracts at 20 mg/ml also showed significant anthelmintic activity. Among all the extracts of A. scholaris, chloroform extract was most potent at concentration 20 mg/ml but less efective than standard drug albendazole. This investigation revealed that all the extracts of A. scholaris showed efficient bactericidal, fungicidal and anthelmintic activity against the test pathogens indicating the medicinal property of A. scholaris.